1997
DOI: 10.1177/0743554897122007
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Connection, Regulation, and Support for Autonomy to Adolescents'Functioning

Abstract: How is adolescent functioning related to experiences of connection, regulation, and supportfor autonomy at home, in school, and with peers? Using datafrom the Maryland Adolescent Growth in Context (MAGIC) study (an ongoing longitudinal study of 1,387 African Amenrican and European American adolescents and theirfamilies), it was found that: (a)family demographic characteristics helped predict only academicperformance; (b) although positive experiences on one indicator predicted positive experiences on the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
192
4
10

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(222 citation statements)
references
References 14 publications
16
192
4
10
Order By: Relevance
“…Petit et al). Conversely, self -report studies have indicated that parents ' granting of psychological autonomy is linked with a range of positive emotional and behavioral outcomes, including less depressed affect and fewer externalizing problems both concurrently and longitudinally (Barber & Olson, 1997 ;Eccles, Early, Frasier, Belansky, & McCarthy, 1997 ;Herman, Dornbusch, Herron, & Herting, 1997 ;Silk et al, 2003 ). Similarly, observations of behavior promoting of cognitive/verbal autonomy while also maintaining relatedness during a family discussion have been linked to lower levels of adolescent depression over time, as rated by observers during a clinical interview (Allen et al, 1994a ).…”
Section: Autonomy Processes Views Of the Self And Internalizing Promentioning
confidence: 99%
See 2 more Smart Citations
“…Petit et al). Conversely, self -report studies have indicated that parents ' granting of psychological autonomy is linked with a range of positive emotional and behavioral outcomes, including less depressed affect and fewer externalizing problems both concurrently and longitudinally (Barber & Olson, 1997 ;Eccles, Early, Frasier, Belansky, & McCarthy, 1997 ;Herman, Dornbusch, Herron, & Herting, 1997 ;Silk et al, 2003 ). Similarly, observations of behavior promoting of cognitive/verbal autonomy while also maintaining relatedness during a family discussion have been linked to lower levels of adolescent depression over time, as rated by observers during a clinical interview (Allen et al, 1994a ).…”
Section: Autonomy Processes Views Of the Self And Internalizing Promentioning
confidence: 99%
“…Research on parental monitoring, behavioral control and behavioral autonomy has indicated consistent links between high levels of monitoring and firm/consistent behavioral control and low levels of problems behaviors during adolescence (Barber et al, 1994 ;Galambos, Barker, & Almeida, 2003 ;Eccles et al, 1997 ;Gray & Steinberg, 1999 ;Hayes et al, 2004;Herman et al, 1997 ;Pettit, Laird, & Dodge, 2001 ). With regard to behavioral autonomy, adolescents appear to benefit from parenting that supports their participation in family decision making, but overly high levels of adolescent behavioral autonomy (as often occur with permissive and/or neglectful parenting) tend to be maladaptive for teens Steinberg, Lamborn, Darling, Mounts, & Dornbusch, 1994 ).…”
Section: Autonomy Processes and Externalizing Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within parent-adolescent and teacher-student relationships, the support of autonomy (e.g., decision-making, personal goal selection), warmth and support, and interactions that promote feelings of competence (e.g., praise, awards and other recognition) foster adolescent engagement, competence and self-regulation (Eccles et al, 1997;Gray & Steinberg, 1999;Skinner et al, 1998). These relationship qualities might also be beneficial when experienced in the workplace.…”
Section: Relationships At Workmentioning
confidence: 99%
“…Il faut cependant mentionner que la mesure de la dépression utilisée dans cette étude ne compte que peu d'items limitant ainsi l'interprétation des résultats. Eccles et al (1997) trouvent que l'encouragement à l'autonomie a un effet sur la dépression, peu importe le sexe, alors que l'encadrement parental n'aurait pas d'effet significatif et l'engagement parental influerait sur la dépression des filles uniquement. Concernant les troubles du comportement, l'engagement et l'encadrement parental seraient des facteurs importants.…”
Section: Style Parental Dépression Troubles Du Comportement Et Risqunclassified